Memorandum of Understanding between the BRAC School of Public Health and UNAIDS Collaborating Centre Agreement (CCA) (2008) - UNAIDS; BRAC University (UNAIDS and BRAC School of Public Health, 2013)
1. Background. 2. Mission and Key functions of UNAIDS and BSPH. 3. Objectives of Collaboration. 4. Principles governing collaboration. 5. Elements of collaboration. 6. Resources. 7. Duration and Amendment of Agreement. 8. Monitoring and follow-up.